Work engagement and occupational future time perspective among Chinese new nurses: the mediating role of career adaptability - Shen, Ying; Song, Fengfeng; Lv, Aini; Su, Yuanyuan; Lu, Le; Song, Yan (Frontiers in Psychology, 2026)
IntroductionThe aim of this study is to investigate the relationship between work engagement, occupational future time perspective (OFTP), and career adaptability among newly graduated nurses (NGNs) in China.MethodsA questionnaire survey was conducted with 316 newly graduated nurses from 20 hospitals across various provinces in China. The survey included measures of work engagement, OFTP, and career adaptability. Structural equation modeling was used to analyze the data and test the mediating role of career adaptability.ResultsIn this study, the mean scores of work engagement, occupational future time perspective and career adaptability among 316 newly graduated were (34.55 ± 10.61), (28.56 ± 8.16), and (68.31 ± 15.77), respectively. The findings indicate that a positive OFTP significantly contributes to higher levels of work engagement among NGNs. Career adaptability was found to mediate the relationship between OFTP and work engagement. Married nurses, those with formal employment contracts, and those with more experience or fewer night shifts reported higher levels of work engagement.ConclusionThis study underscores the importance of a positive OFTP in enhancing work engagement among NGNs. Career adaptability plays a crucial mediating role, suggesting that interventions aimed at improving adaptability could amplify the positive effects of a positive OFTP on work engagement.